Exploring the association between atmospheric pollutants and preterm birth risk in a river valley city - Gu, Jiajia; Li, Jimin; Liu, Lang; Cao, Meiying; Tian, Xi; Wang, Zeqi; He, Jinwei (Frontiers in Public Health, 2024)
To investigate the association between exposure to atmospheric pollutants and preterm birth in a river valley-type city and its critical exposure windows.A retrospective cohort study was used to collect data from the medical records of preterm and full-term deliveries in two hospitals in urban areas of a typical river valley-type city from January 2018 to December 2019. A total of 7288 cases were included in the study with general information such as pregnancy times, the number of cesarean sections, occupation, season of conception, and regularity of the menstrual cycle, and confounding factors affecting preterm birth were inferred using the chisquare test. The effects of exposure to each pollutant, including Particulate Matter 2.5 (PM2.5), Particulate Matter 10 (PM10), Nitrogen Dioxide (NO2), Sulfur Dioxide (SO2), Carbon Monoxide (CO) and Ozone (O3), during pregnancy on preterm birth and the main exposure windows were explored by establishing a logistic regression model with pollutants introduced as continuous variables.Maternal age, pregnancy times, number of births, number of cesarean sections, season of conception, complications diseases, comorbidities diseases, hypertension disorder of pregnancy, and neonatal low birth weight of the newborn were significantly different between preterm and term pregnant women. Logistic regression analysis after adjusting for the above confounders showed that the risk of preterm birth increases by 0.9%,0.6%,2.4% in T2 and by 1.0%, 0.9%, 2.5% in T3 for each 10 μg/m 3 increase in PM2.5, PM10, NO2 concentrations, respectively. The risk of preterm birth increases by 4.3% in T2 for each 10 μg/m 3 increase in SO2 concentrations. The risk of preterm birth increases by 123.5% in T2 and increases by 188.5% in T3 for each 10 mg/m 3 increase in CO concentrations.Maternal exposure to PM2.5, PM10, NO2, CO was associated with increased risk on preterm birth in mid-pregnancy (T2) and late pregnancy (T3), SO2 exposure was associated with increased risk on preterm birth in mid-pregnancy(T2).